Modelling the accumulation of PSP toxins in Thau Lagoon oysters (Crassostrea gigas) from trials using mixed cultures of Alexandrium catenella and Thalassiosira weissflogii - Lassus, Patrick; Amzil, Zouher; Baron, Regis; Sechet, Veronique; Barille, Laurent; Abadie, Eric; Bardouil, Michele; Sibat, Manoella; Truquet, Philippe; Berard, Jean-baptiste; Gueguen, Marielle (EDP Sciences, 2007)
In October and November 2003 a bloom of the toxic dinoflagellate Alexandrium catenella was observed in the North-east zone of Thau lagoon (French Mediterranean coast). Sea water samples were collected every hours to evaluate time-related variations of phytoplankton concentrations and to compare the relative ratio of A. catenella versus other phytoplankton species during the outbreak. From these observations, trials using recirculated sea water systems were performed to: i) evaluate the physiological effects on oyster of increasing proportions of A. catenella within a mixed microalgal diet where the non-toxic diatom Thalassiosira weissflogii was present at concentration: 1500 cells ml(-1), ii) compare the effect of two temperatures (12 degrees C and 18 degrees C) on paralytic toxin accumulation rates in oyster flesh by ion-pairing high performance liquid chromatography (IP-HPLC) detection, iii) analyse toxin biotransformation during the contamination process, iv) evaluate the role of the different types of oyster tissue on the bioaccumulation mechanism. The results showed: i) a significant e. ect of temperature increase on clearance rate and toxin uptake, ii) no detectable time-related effects of toxic algal food on pre-ingestion sorting or on toxin profiles in oyster flesh, iii) either negative or positive effects of A. catenella concentrations on toxin uptake ("threshold" effect), iv) high amounts of toxins in the digestive gland, accounting for more than 80% of overall shellfish toxicity. The daily amount of toxins (Q(tox)) taken up by each oyster was evaluated by means of a global one-compartment model. However a two-compartment model finally gave the best match with real contamination kinetics, since it integrated both toxins sequestered in oyster tissues and toxins moving in through the digestive tract. En octobre et novembre 2003, une prolifération du dinoflagellé toxique Alexandrium catenella a été observée dans la partie nord-est de l'étang de Thau (côtes méditerranéennes françaises). Des échantillons ...